Kişiyi hürriyetinden yoksun kılma suçu - Akın, Özgül (My University, 2009)
yetinden Yoksun Kılma Suçu ÖZET KİŞİYİ HÜRRİYETİNDEN YOKSUN KILMA SUÇU Kişi özgürlüğü, yıllardan beri üzerinde en çok durulan konuların başında yer almaktadır. Bunun temel nedeni de kişi özgürlüğünün diğer tüm özgürlüklerin temelini oluşturmasıdır. Kişi özgürlüğünün bireylere ve devlete karşı korunması da ceza kanunu ile güvence altına alınması ve yaptırıma bağlanması ile mümkündür. Araştırmada Türk Ceza Kanunu’nun 109’ uncu maddesinde yer alan kişiyi hürriyetinden yoksun kılma suçu incelenmiştir. Tez üç bölümden oluşmuştur. Birinci bölümde hürriyet kavramı üzerinde durulduktan sonra suçun tarihsel gelişimi ve Türk Hukukundaki durumu açıklanmıştır. Suçun Türk Hukuku’nda düzenlenişi anlatılırken, kişiyi hürriyetinden yoksun kılma suçunun ele alınışı açısından 765 sayılı TCK ile 5237 sayılı TCK arasındaki farklara yer verilmiştir. İkinci bölümde 5237 sayılı TCK’ nın suç teorisi çerçevesinde suçun unsurları kişiyi hürriyetinden yoksun kılma suçu açısından değerlendirilmiştir. Üçüncü bölümde ise suçun özel görünüş şekilleri, soruşturma ve kovuşturma usulü ve yaptırımı ele alınmıştır.

“A TREATISE ON ABU YOUSUF’S KITAB AL-ATHAR IN PERSPECTIVE OF HADITH SCIENCE” Prophet’s hadiths were inscribed when he was alive. It is seen that by the second hidji century all books those collecting Prophet’s hadiths were classified. One of the pioneer books in that area was Abu Yousuf’s book, Kitab al-athar. Including 1152 hadiths, the book was mostly made of the narrated hadiths by Abu Yousuf from his master Abu Hanifa. In that sense, it is also can be regarded as Abu Hanifa’s musnad. Abu Yousuf classified hadiths those he transmitted from his master according to Fiqh chapters (bab). Hence, Kitab al-athar is considered as an early musannaf. This work is very important in which it shows Abu Hanifa and Abu Yusuf’s accumulation and consequently Hanafis’ accumulation concerning hadith and sunnah and Hanafis’ concept of sunnah and hadith. This book states maktu’, marfu’ and mawqouf hadiths together. However, mawqouf hadiths are more than marfu hadiths. Marfu’ hadiths are nearly half of all. Maktu’s are mostly fatwas transmitted from Ibrahim al-Nakhai. Maktu’ hadith are being imputed to marfu’ and mawqouf hadiths. Collected hadiths in this book are mostly concerning religious rituals. There are a bunch of hadiths regarding social interactions and moral issues. Kitab al-athar is seen mostly as a catechism due to the plenty of narratives. Key words: hadith, athar, kitab al-athar, Abu Yousuf, Abû Hanifa, musannaf, musnad
Keywords: Hukuk; Kamu Hukuku; Kişi Hakları; Özgürlük